Zinc, Copper, and Aluminium Dynamics in Urban In-Channel Stormwater Treatment Systems Under Varying Groundwater Conditions - Fabio C. Silveira; Thomas A. Cochrane; Ricardo Bello-Mendoza; Frances Charters (Air, Soil and Water Research)
The effective removal of excess heavy metals from surface stormwater is an important environmental goal due to their potential toxicity to aquatic organisms. In-channel stormwater treatment systems (ICSTS) are often used to remove pollutants from stormwater-impacted streams. However, the impact of hydraulic conditions on treatment performance is not well characterised. This research investigates the impact of varying groundwater conditions and bed media hydraulic conductivity on the dynamics of aluminium (Al), copper (Cu), and zinc (Zn) in ICSTS. Experiments conducted in a 19-m flume with gravel, bed media, and surface water under seepage, drainage, and neutral groundwater conditions revealed significant variations in heavy metal retention and release. Under groundwater seepage, there was an average decrease of dissolved Zn in the outlet and an increase in both total and dissolved Cu (5% for Zn; 16% for Cu) when using high hydraulic conductivity media (HH). Low hydraulic conductivity media (LH) under seepage led to a greater increase of dissolved and total Zn and Cu (7% for Zn; 44%–56% for Cu). Under drainage conditions, there was a decrease in dissolved Zn and Cu loads (14% for Zn; 15%–18% for Cu) with HH media and greater variation in pH and redox potential (Eh). Drainage with LH media resulted in lower Zn loads (8%) and an increase in total and dissolved Cu loads (34%–65%). Lower Zn concentrations were also observed in the groundwater (25%–46% decrease) after draining through the bed media, while Cu increased around 200% but only when using LH media. Total aluminium increased in concentration and loads while dissolved Al decreased in all scenarios. This research highlights the importance of designing ICSTS that promote drainage and high hydraulic conductivity bed sediment to enhance metal retention. It also emphasises the need for ongoing monitoring and maintenance to prevent clogging, contaminant release, and long-term performance decline.